First European quality of life survey life satisfaction, happiness and sense of belonging - Bohnke, Petra; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2005)
Promoting people's well-being is a primary goal of European social policy: happy, satisfied, fulfilled and engaged citizens nurture flourishing European societies. However, interventions to promote subjective well-being have not been explicitly at the centre of a European social policy strategy up to now and research results on subjective well-being often fail to underline their major policy implications. The subject of well-being is well developed in scientific terms, but little is known of its distribution and determinants in the new Member States (NMS) compared with the EU15. This report contributes to a better understanding of subjective well-being in an enlarged Europe and goes beyond previous research activities in this field by emphasising social as well as societal living conditions as major contributors to life satisfaction, happiness and belonging.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Electronic books